Cancer screening education: can it change knowledge and attitudes among culturally and linguistically diverse communities in Queensland, Australia?. (29th June 2016) - Cullerton, Katherine; Gallegos, Danielle; Ashley, Ella; Do, Hong; Voloschenko, Anna; Fleming, MaryLou; Ramsey, Rebecca; Gould, Trish
Abstract : Issue addressed: Screening for cancer of the cervix, breast and bowel can reduce morbidity and mortality. Low participation rates in cancer screening have been identified among migrant communities internationally. Attempting to improve low rates of cancer screening, the Ethnic Communities Council of Queensland developed a pilot Cancer Screening Education Program for breast, bowel and cervical cancer. This study determines the impact of education sessions on knowledge, attitudes and intentions to participate in screening for culturally and linguistically diverse (CALD) communities living in Brisbane, Queensland. Methods: Seven CALD groups (Arabic‐speaking, Bosnian, South Asian (including Indian and Bhutanese), Samoan and Pacific Island, Spanish‐speaking, Sudanese and Vietnamese) participated in a culturally‐tailored cancer screening education pilot program that was developed using the Health Belief Model. A pre‐ and post‐education evaluation session measured changes in knowledge, attitudes and intention related to breast, bowel and cervical cancer and screening. The evaluation focussed on perceived susceptibility, perceived seriousness and the target population's beliefs about reducing risk by cancer screening. Results: There were 159 participants in the three cancer screening education sessions. Overall participants' knowledge increased, some attitudes toward participation in cancer screening became more positive and intent to participate in future screening increased (n = 146). Conclusion: These results indicate the importance of developing screening approaches that address the barriers to participation among CALD communities and that a culturally‐tailored education program is effective in improving knowledge, attitudes about and intentions to participate in cancer screening. So what?: It is important that culturally‐tailored programs are developed in conjunction with communities to improve health outcomes. Abstract : Low participation rates in cancer screening have been identified among migrants internationally. To address this, the Ethnic Communities Council of Queensland developed an education program for breast, bowel and cervical cancer screening. After participating in the program, participants' knowledge increased; some attitudes toward participation in cancer screening became more positive; and intent to participate in future screening increased. These results indicate the importance of developing screening approaches that address the barriers to participation among culturally and linguistically diverse communities.